Analisis Ability to Pay dan Willingness To Pay Non-Komuter untuk Penentuan Tarif pada Perencanaan Layanan Operasi Kereta Api Makassar – Parepare - Ramli, Muhammad Isran; Mullyani, Savitri Prasandi; Adisasmita, Sakti Adji; Abdurrahman, Muhammad Asad; Yatmar, Hajriyanti (Jurnal Ilmiah Rekayasa Sipil, 2023)
The upcoming Railway of Makassar-Parepare needs to determine the appropriate tariff. The tariff should be affordable and attractive people to using the public transport. In addition to considering the train fare that has been determined by considering the operational costs of the operator, it is also necessary to consider the Ability to Pay (ATP) and Willingness to Pay (WTP) values ​​for prospective train users, especially non-commuters. The purpose of this study was to analyze the value of ATP and WTP for prospective users of the Makassar - Parepare train service, especially for non-commuting trips. The data collection method in this study was conducted through a primary data survey using questionnaires or direct interviews with respondents who have the potential to use the Makassar - Parepare Railway. The respondent sampling process is based on each sub-district along the Makassar-Parepare railway line. The research data obtained were then analyzed further to see the characteristics of the respondents, ATP values, and WTP values. The results of the analysis on fares for trains with ATP and WTP values ​​at a maximum value of Rp. 468,-/ km with 58% of respondents. The fare value for the total length of the Makassar-Parepare route is 141 km, which is Rp. 65,988,-. The results of this study also show that the ATP value is lower than the fare for public transportation using a mini bus with the same distance on the Makassar-Parepare route with a value of Rp. 120.000,- so that the potential tariff in its determination must still consider the service received.